The Sea Their Graves : An Archaeology of Death and Remembrance in Maritime Culture - Stewart, David J. (David James), 1968- (Book collections on Project MUSE., 2011)
Based on a study of more than 2,100 gravestones and monuments in North America and the United Kingdom erected between the seventeenth and late twentieth centuries, David Stewart expands the use of nautical archaeology into terrestrial environments.